2022
DOI: 10.1038/s41434-022-00376-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential of an anti-bevacizumab idiotype scFv DNA-based immunization to elicit VEGF-binding antibody response

Abstract: Anti-idiotype antibodies have been considered for vaccination approaches against different diseases, including cancers. Based on that, we previously described an anti-bevacizumab idiotype monoclonal antibody, 10.D7, that revealed detectable antitumor effects on a vascular endothelial growth factor (VEGF)-dependent tumor model. Herein, we evaluated the possible applicability of a single-chain variable fragment (scFv) for the 10.D7 antibody in a gene immunization strategy. After checking that mammalian cells tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Related studies have shown that adjuvant therapy with targeted drugs can improve efficacy by effectively reducing the damage of chemotherapy to normal cells in the body[ 13 - 15 ]. Bevacizumab (BEV), a monoclonal antibody with targeted effects, can inhibit tumor growth and metastasis by inhibiting the formation of tumor neovascularization caused by the binding of vascular endothelial growth factor (VEGF) to its receptor[ 16 , 17 ]. Research has provided evidence that the utilization of BEV in conjunction with adjuvant chemotherapy can significantly enhance long-term efficacy[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have shown that adjuvant therapy with targeted drugs can improve efficacy by effectively reducing the damage of chemotherapy to normal cells in the body[ 13 - 15 ]. Bevacizumab (BEV), a monoclonal antibody with targeted effects, can inhibit tumor growth and metastasis by inhibiting the formation of tumor neovascularization caused by the binding of vascular endothelial growth factor (VEGF) to its receptor[ 16 , 17 ]. Research has provided evidence that the utilization of BEV in conjunction with adjuvant chemotherapy can significantly enhance long-term efficacy[ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…ScFv contains the complete antigen-binding domain of an intact antibody. ScFv fragments have found great medical applications [12]. Several approaches have been employed to increase the affinity, avidity and structural stability related to these antibody fragments [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…ScFv fragments have found great medical applications [12]. Several approaches have been employed to increase the affinity, avidity and structural stability related to these antibody fragments [12,13]. Among all strategies to engineer ScFv antibodies there is no attempt to use the retro-protein approach.…”
Section: Introductionmentioning
confidence: 99%